Requena - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1985)
SPANISH: La fotografía muestra el camino a la cruz del Peladillo un monumento histórico de la fé cristiana de Requena.
ENGLISH: The photograph shows the path to the cross of Peladillo, a historical monument of the Christian faith in Requena.

SPANISH: La fotografía muestra el camino a la cruz del Peladillo un monumento histórico de la fé cristiana de Requena.
ENGLISH: The photograph shows the path to the cross of Peladillo, a historical monument of the Christian faith in Requena.
Requena
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos